Influence of Silicon Nanosheet (SiNS) on the Toughness of Biphasic Calcium Phosphate (BCP) Composites (Fracture and Structural Integrity, 2025)
Recent developments in the field of replacing and generating human tissues have led to a renewed interest in finding alternative materials or composites that enhance the development of these technologies. Therefore, the main goal of the current study was to investigate the effect of adding a nanomaterial with a two-dimensional structure called silicene, which is also known as silicon nanosheet (SiNS) on among the best leaders in biomaterials which are HA and TCP. This investigation has examined the fracture toughness property and flexural strength to explore the importance of adopting the nanomaterials. Through this paper, silicene has been synthesised using chemical reactions and added in various weight ratios of (1,3, and 5) % to BCP composites which are produced with various weight ratios of HA and TCP. Based on the findings, adding SiNS by a percentage ranging from 1% to 3% to the BCP composites increased their toughness, and flexural strength from 33 to 87.64 %, and 15 to 60 % respectively. However, as some percentages climbed and others fell in toughness or flexural strength, the results of the samples containing 5% of SiNS started to differ somewhat.This is due to that the filler (SiNS) has the capacity to prevent cracks from growing while also preserving crystalline tissue, which makes it a crucial defence against fracture propagation. This increase gave sufficient motivation to adopt this composition and addition in biomedical applications.
Keywords: Silicene; Bioceramic composite; Silicon nanosheet; Fracture toughness; Flexural strength; BCP